2014
DOI: 10.1631/jzus.a1300331
|View full text |Cite
|
Sign up to set email alerts
|

A modified creep index and its application to viscoplastic modelling of soft clays

Abstract: Conventional consolidation tests on reconstituted specimens of numerous natural soft clays show a decreasing of creep index C e with increasing soil density. Based on all selected and conducted experimental results, a modified creep index C e * defined in double logarithmic plane lge-lgt, was plotted for various clays, from which C e * can be assumed as a constant for different soil densities. Then, the modified creep index was applied to a newly developed elastic viscoplastic model. In this way, the modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Figure 12 shows a tendency for an increasing C ae with the increasing LL, PI and SOM. These results were consistent with those of Bjerrum et al [8], Nakase et al [53], Yin [70], Jesmani et al [32] and Zhu et al [82]. Present study and the results of the above-mentioned researchers showed that plasticity and organic matter to a great extent influence the timedependent behaviour of fine-grained soils.…”
Section: Coefficient Of Secondary Compression Change Index Msupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 12 shows a tendency for an increasing C ae with the increasing LL, PI and SOM. These results were consistent with those of Bjerrum et al [8], Nakase et al [53], Yin [70], Jesmani et al [32] and Zhu et al [82]. Present study and the results of the above-mentioned researchers showed that plasticity and organic matter to a great extent influence the timedependent behaviour of fine-grained soils.…”
Section: Coefficient Of Secondary Compression Change Index Msupporting
confidence: 93%
“…To overcome the limitation of the logarithmic function, some nonlinear creep formulations have been proposed. Yin et al [73] formulated a nonlinear expression of C ae with volumetric strain and time that considers the influence of the bulk density q and e. Wu et al [68] also considered consecutively decreasing C ae related to the q. Zhu et al [82] and Yin et al [74] demonstrated a decreasing C ae as q increased. They introduced a modified C ae * , defined in a double-logarithmic plane.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the reduction of the σ′ p0 and σ′ pi0 are the pre-consolidated pressures for the natural sample and reconstituted sample, respectively; K nc is the coefficient of lateral pressure for normally consolidated clay apparent secondary compression coefficient through inter-particle debonding can be reproduced. The model's predictive ability has been validated for various soft sensitive clays (Yin et al, 2010a;2011a;Karstunen and Yin, 2010;Zhu et al, 2014). Therefore, this model was adopted in this study.…”
Section: Adopted and Enhanced Constitutive Modelmentioning
confidence: 99%
“…Clayey soils usually display significant creep deformation in the form of prolonged settlements of foundations, tilts of geotechnical structures, or slippage of slopes and embankments, for instance (i.e. Mesri & Choi, 1985;Tavenas & Leroueil, 1981;O'Reilly et al, 1991;Rowe & Hinchberger, 1998;Mitchell & Soga, 2005;Karstunen & Yin, 2010;Yin et al, 2015Yin et al, , 2017Zhu et al 2014). Generally, the mechanical behavior of clay is determined by the microstructural state of the material and its evolution.…”
Section: Introductionmentioning
confidence: 99%